(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In this article, the effects of using a highly swelling hydrogel polymer compound, synthesized from local raw materials, as a water-saving irrigation technology at different application rates in the cultivation of the winter wheat variety "Starshina" on gray-brown, light sandy, non-saline soils in the newly developed desert zone of the Bukhara region are discussed. The obtained results are also presented.